A Planet in Crisis, Law on Trial: Toward a Just and Inclusive Geopolitics of Sustainability - Sugiyono, Leony Franaisca; Anandatia, Via; Nandini, Gusti (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The global ecological crisis, marked by climate change, biodiversity loss, and natural resource degradation, has revealed the limitations of existing legal frameworks in ensuring environmental sustainability. While international environmental law has developed significantly through instruments such as the Kyoto Protocol and the Paris Agreement, its implementation remains deeply uneven due to geopolitical power imbalances, historical responsibilities, and disparities in technical and financial capacities between the Global North and South. This study critically examines the intersection of environmental law and global geopolitics, arguing that legal mechanisms alone are insufficient without addressing underlying structural inequalities. Employing a multidisciplinary approach that integrates international law, political ecology, and sustainability studies, the research highlights three major areas: the evolution of international legal instruments, the geopolitical asymmetries in their implementation, and the emergence of inclusive and just sustainability initiatives. Furthermore, the study underscores the transformative role of non-state actors, particularly indigenous communities, civil society organizations, and transnational grassroots movements, in shaping global environmental governance. The novelty of this research lies in its emphasis on law as a political and normative tool to challenge dominant paradigms and reconstruct a more equitable global environmental order. The findings offer strategic insights for policymakers, legal scholars, and advocacy groups committed to promoting ecological justice in the era of the climate crisis.